(untitled) (Cadernos de Sociomuseologia, 2021)
In this text I discuss the visibility actions of LGBT population in Belo Horizonte-MG museums, and I also present the curricular academic activity, with the theme of gender diversity, which is offered in the UFMG museology course. I believe that the museums can contribute to overcoming phobias of sexual condition, identity and gender. In this perspective, what is importante is the museal processes, I mean, the inquiries through of collections, the procedures and also the methodologies based on a problem. I analyze the actions implemented, in order to highlight the experiences of the LGBT population, through the programming of the Museums of Belo Horizonte in the last 10 years. The period coincides with the creation of the museology course at the Federal University of Minas Gerais. I even emphasize the importance of the debate on gender and diversity in the academic activities of this course. As a conclusion of this study, I present the necessity for a greater investment in political and affirmative museology, capable of combating homolesbotransphobia, thus seeking a fair and egalitarian society. Keywords: Museums; Museology; LGBT; Diversity